Marketing Strategy In An Effort To Increase The Number Of Customers In Baitul Tamwil Hidayatullah Makassar - Merry Sudictar; Sayyidaturrofifah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The main problem in this study is how the marketing steps of Baitul Tamwil Hidayatullah Makassar in Increasing the Number of Customers and what are the supporting or inhibiting factors that may occur in Baitul Tamwil Hidayatullah Makassar in the implementation of marketing strategies. This type of research uses a qualitative descriptive research method with a field research approach. The type of data used is primary data obtained from the results of interviews with five informants, from managers, admins and customers of Baitul Tamwil Hidayatullah, secondary data that is analyzed through data collection, data reduction, presentation and conclusion drawn. The results of this study show that the marketing of Baitul Tamwil Hidayatullah Makassar in increasing the number of customers is only from friend to friend. The supporting factors of Baitul Tamwil Hidayatullah Makassar in increasing the number of customers are the teamwork and involvement and enthusiasm of other customers in marketing Baitul Tamwil Hidayatullah products. Regarding the inhibiting factors, namely services, financial literacy, and lack of Human Resources (HR). The implication in this study is that Baitul Tamwil Hidayatullah Makassar needs to improve its strategy through the distribution of brochures, socialization from school to school, increasing branches in the regions, and providing products that are most needed by the community. Meanwhile, the suggestion for Baitul Tamwil Hidayatullah Makassar is that it is expected to increase the evaluation of the implementation of continuous promotion and socialization activities, improve service quality, create jobs so that there is no shortage of manpower, utilize social media such as Instagram, TikTok, and so on so that the outside public understands about sharia financing and what products BTH has.